Evaluation of antidiabetic activity in Corallocarpus epigaeus rhizomes - Gnananath, Kattamanchi; Reddy, Kontham Ramakanth; Kumar, Gudur Pavan; Krishna, Bheemanapally; Reddy, Karka Srinivas; Kumar, Avvari Sanjeeva (International Current Pharmaceutical Journal, 2013)
From these results it can be understood that plant extract showing its pharmacological action on diabetes between the time intervals of 1-2 hr after its administration. This is exactly what the action that is being observed from the standard Glibenclamide group which also shown its action at its 1-2 hr of administration to the animals. Here the statistically significant action of the higher dose of plant extract can be compared with that of the standard Glibenclamide group. From these results it can be understood that the plant extract is capable of inhibiting the elevation of blood glucose level to the extent of the action that has been shown by the standard Glibenclamide group. Particularly at the time interval of 2-4 hr both the Glibenclamide and plant extract at its high dose group that is 400 mg/kg has been significantly inhibited the elevation of the blood glucose levels in the animals. DOI: http://dx.doi.org/10.3329/icpj.v2i3.13581 International Current Pharmaceutical Journal, February 2013, 2(3): 53-56